2021
DOI: 10.1088/1742-6596/1842/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Learning Obstacle of Addition Operation Whole Number in Elementary Schools

Abstract: This study aims to analyze the learning obstacle of students in elementary schools on the addition operation whole number. The research method used is a qualitative descriptive research method. The subjects of this study were 15 elementary school students who were selected using a purposive sampling technique. Data collection techniques include non-participatory observation, test of addition operation whole number in the form of story questions, unstructured interviews, and documentation studies. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Furthermore, the width of the garden determined is divided by three to get a garden width of 8 m. The interview results indicate that the students did not understand how to convert the problem into a mathematical equation. These results are in line with previous research that found that students had difficulty understanding the meaning of the questions and had difficulty translating questions into math sentences (Sidik et al, 2021).…”
Section: Table 2 Student Achievements For Problem Number 2: Convertingsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the width of the garden determined is divided by three to get a garden width of 8 m. The interview results indicate that the students did not understand how to convert the problem into a mathematical equation. These results are in line with previous research that found that students had difficulty understanding the meaning of the questions and had difficulty translating questions into math sentences (Sidik et al, 2021).…”
Section: Table 2 Student Achievements For Problem Number 2: Convertingsupporting
confidence: 92%
“…Supported by the interview information, these students understand that 1 kg equal 10 ounces. A middle school students' understanding of using units of measure relates to the students' understanding of numbers and measurements (Sidik et al, 2021). In contrast, units of measurement are necessary for conceptual understanding of size and scale (Delgado, 2010).…”
Section: Studentmentioning
confidence: 99%
“…In addition to making the operation of the media as easy as possible, the researcher also provides instructions for use in the form of videos to help users who feel confused and instructions for use are equipped with explanations to instil the concept of addition and subtraction based on place value. This aims to instill the right concepts for students who are just learning composing addition and subtraction, against the background of Sidik's research which found the results that students' learning difficulties in doing addition and subtraction came from applied aspects, misunderstood the problem and misunderstood the place value in compound addition [16].…”
Section: Discussionmentioning
confidence: 99%
“…e ability of students to understand algebraic thinking problems is also influenced by their experience with the variants of questions given during the learning process. Problems or patterns of questions that students learn in the addition operation material are usually about patterns (a + b � □) [12]. In the addition operation, there are at least two conditions, namely, the problems with the unknown change part (a + □ � c) and the unknown initial part (□ + b � c).…”
Section: Introductionmentioning
confidence: 99%